PENGARUH SUKU BUNGA BANK INDONESIA DAN EARNING PER SHARE TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 S.D 2017 - Tati Martiningsih; Syakdanur Nas; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to examine the influence of Bank Indonesia Interest Rates and Earning per Share on the Chemical Sector Manufacturing Company Stocks Return listed on the Indonesia Stock Exchange in 2013 to 2017 period. This research used descriptive quantitative methods with correlational research design and multiple regression analysis. The data used in this research were secondary data, i.e the company's annual report. The population in this research was all Manufacturing Companies in the Basic and Chemical Industry sectors which listed on the Indonesia Stock Exchange (IDX) in 2013 to 2017 were 68 companies with purposive sampling techniques which have certain criteria. The total samples in this research were 9 chemical sector companies. Based on the research finding, it found that Bank Indonesia interest rates and Earning per Share were simultaneously influence on the stock Returns. The influence magnitude of Bank Indonesia interest rates and Income per Share on Stock Returns was 27.1% while the rest 72.9% were influenced by other variables which is not explained in this research. Furthermore, the research finding partially showed that Bank Indonesia interest rates have a significant influence on the stock returns, while Earning per Share has no significant influence.Key Words: BI Interest Rate, Earning per Share, and Stock Return.